The Impact Of Vitamin D Supplementation During Pregnancy On Preeclampsia Risk: A Comprehensive Systematic Review - Mutia Juliana (International Medical Journal Corp. Ltd, 2024)
Background: Studies suggest vitamin D's potential role in reducing early-onset preeclampsia risk through improved endothelial function and reduced oxidative stress. This systematic review aims to evaluate the impact of vitamin D supplementation on the risk of preeclampsia based on literatures of the last 10 years. Methods: The review adhered to PRISMA 2020 standards and analyzed full-text English literature from 2014 to 2024. It excluded editorials, review papers from the same journal, and submissions lacking a DOI. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 500 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, five articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: Vitamin D plays a crucial role in various physiological processes, including calcium homeostasis, immune modulation, and vascular function, all of which are implicated in the pathogenesis of preeclampsia.